2019
DOI: 10.31857/s0869-56524842224-227
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of control of differentiation of regulatory t-lymphocytes by exogenous melatonin

Abstract: We investigated the role of epiphyseal hormone melatonin in the differentiation of naive CD4+T cells into regulatory T cells (Treg). The hormone at physiological and pharmacological concentrations inhibited Treg differentiation, decreasing both the proportion of CD4+FOXP3+ cells in the culture and the level of TGF‑β, the key cytokine for this T cell subpopulation. The inhibitory effect of exogenous melatonin was due to its interaction with the membrane receptors MT1 and MT2. At the same time, the signals reali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Gut-derived Treg cells have been confirmed to feature in the prognosis of stroke, and studies have confirmed that programmed death protein 1 (PD-1) and CC-chemokine ligand 28 (CCL28) regulate Treg cells (Wang P. et al, 2019;He et al, 2021). In addition, melatonin also has a regulatory effect on Treg cells (Álvarez-Sánchez et al, 2015;Glebezdina et al, 2019). Therefore, the combined effect of melatonin and gut microbiota whether further affect the prognosis of SCI through Treg cells is worthy of in-depth study.…”
Section: Discussionmentioning
confidence: 99%
“…Gut-derived Treg cells have been confirmed to feature in the prognosis of stroke, and studies have confirmed that programmed death protein 1 (PD-1) and CC-chemokine ligand 28 (CCL28) regulate Treg cells (Wang P. et al, 2019;He et al, 2021). In addition, melatonin also has a regulatory effect on Treg cells (Álvarez-Sánchez et al, 2015;Glebezdina et al, 2019). Therefore, the combined effect of melatonin and gut microbiota whether further affect the prognosis of SCI through Treg cells is worthy of in-depth study.…”
Section: Discussionmentioning
confidence: 99%
“…to reduce the rate of insulin secretion after receptor activation [60]. MT receptors have also been identified in leukocytes [61][62][63] and melatonin is suggested to modulate (or regulate) the immune system by (for example) stimulating lymphocytes via these receptors, predominantly via the MT2 receptor [64]. Complete removal of the pineal gland causes partial deterioration in the immune responses of rats [65,66], and administration of melatonin in pinealectomized animals reverses the negative effect on immune responses [66].…”
Section: Discussionmentioning
confidence: 99%